2009
DOI: 10.1007/s00330-009-1335-4
|View full text |Cite
|
Sign up to set email alerts
|

Real-time US elastography in the differentiation of suspicious microcalcifications on mammography

Abstract: The purpose of this study was to retrospectively evaluate the use of US elastography in the differentiation of mammographically detected suspicious microcalcifications, using histology as the reference standard. Between May 2006 and April 2007, real-time US elasticity images were obtained in 77 patients (age range, 24-67 years; mean, 46 years) with 77 mammographically detected areas of microcalcifications (42 benign and 35 malignant lesions) prior to needle biopsy. Two experienced radiologists reviewed cine cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 20 publications
1
16
0
1
Order By: Relevance
“…Fleury Ede et al [23] proposed an elastographic classification system (scales 1-4) using the image of the lesion not only before and during compression, but also after parenchymal decompression and its correlation with the respective histological result. Cho [24] used a three-point scale because lesions with microcalcification, in contrast to solid mass lesions, tended to show less strain difference from the surrounding parenchyma. In addition, the cutoff value of the ES fivepoint systems was different in four studies [18,27,33,34], but observer because of the lack of data reported, subgroup analysis was not possible.…”
Section: Discussionmentioning
confidence: 99%
“…Fleury Ede et al [23] proposed an elastographic classification system (scales 1-4) using the image of the lesion not only before and during compression, but also after parenchymal decompression and its correlation with the respective histological result. Cho [24] used a three-point scale because lesions with microcalcification, in contrast to solid mass lesions, tended to show less strain difference from the surrounding parenchyma. In addition, the cutoff value of the ES fivepoint systems was different in four studies [18,27,33,34], but observer because of the lack of data reported, subgroup analysis was not possible.…”
Section: Discussionmentioning
confidence: 99%
“…Imaging the elasticity of the lesions makes it easier to detect and characterise them, and also to estimate their size [17][18][19]. In the present study, RTE was carried out with colour coding and real-time assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies advocate using ultrasound as the preferred method of predicting the real histopathological tumour size, although most studies have found that ultrasound underestimates the size of breast lesions [6,8,10]. However, the published studies [6,8,[10][11][12][13][14][15][16] may not reflect current technical standards in mammography and ultrasound, as compound imaging and real-time elastography in particular, as a quite new technique in breast diagnosis, may now allow more accurate tumour size estimation [17][18][19][20][21][22][23][24]. Elastography is able to image the elasticity of soft tissues [21].…”
Section: Introductionmentioning
confidence: 87%
“…And a score of 3 indicated no strain in the entire hypoechoic lesion, i.e., the entire lesion was blue. This scoring system was modified from a five-point scale reported in previous research [16] and was found to be useful in differentiating benign from malignant lesions [24].…”
Section: Image Evaluationmentioning
confidence: 99%